Who Moves Up the Job Ladder? - Haltiwanger, John; Hyatt, Henry; McEntarfer, Erika (Journal of Labor Economics, 2018)
In this paper, we use linked employer-employee data to study the reallocation of heterogeneous workers between heterogeneous firms. We build on recent evidence of a cyclical job ladder that reallocates workers from low-productivity to high-productivity firms through job-to-job moves. In this paper, we turn to the question of who moves up this job ladder and the implications for worker sorting across firms. Not surprisingly, we find that job-to-job moves reallocate younger workers disproportionately from less productive to more productive firms. More surprisingly, especially in the context of the recent literature on assortative matching with on-the-job search, we find that job-to-job moves disproportionately reallocate less educated workers up the job ladder. This finding holds even though we find that more educated workers are more likely to work with more productive firms. We find that while highly educated workers are less likely to match to low-productivity firms, they are also less likely to separate from them, with less educated workers more likely to separate to a better employer in expansions and to be shaken off the ladder (separate to nonemployment) in contractions. Our findings underscore the cyclical role job-to-job moves play in matching workers to better-paying employers.